Organizational and economic support economic business security in agriculture - Карпенко, Ольга Володимирівна (Technology audit and production reserves, 2015)
The article analyzes and identifies the key organizational and economic problems of ensureng economic security business. Despite the depth of the current economic developments on theoretical and methodological provisions are quite vulnerable legal framework governing the organizational and economic support economic security of entrepreneurship in agriculture. Economic security business should be viewed as a set of principles, methods and ways in which ensured economic development, competitiveness and sustainability of the enterprise, the protection of its resources, the ability to adequately and without substantial losses to respond to changing internal and external environment. Based on the analysis highlights the main problems of organizational and economic support economic security of entrepreneurship in agriculture: lack of integrated strategic development programs corresponding to their level of funding and lack of innovative database development; limited access to credit and lack of civilized legal framework in lending; the lack of state orders for products and services for small business; high level of red tape and bureaucratic system and total control of the tax and other regulatory authorities.